Three new genera of large marsh beetles (Coleoptera: Scirtidae) from Valdivian temperate rain forests of southern South America - Ruta, Rafał (Zootaxa, 2021)
The present paper fills a gap in the knowledge of the largest marsh beetles in the Neotropics. Argelodes gen. nov., Solierodes gen. nov. and Mucronotus gen. nov. are described from Southern South America. Argelodes and Solierodes are monotypic, contain Argelodes magnificus sp. nov. and Solierodes rousseli (Solier, 1849) comb. nov., while Mucronotus contains five species: Mucronotus velutinus (Solier, 1849) comb. nov., M. schwabei (Pic, 1938) comb. nov., and three newly described ones—M. enigmaticus sp. nov., M. patagonicus sp. nov., and M. valdivianus sp. nov. Affinities of newly described genera with Australian taxa are briefly discussed. Pronotal modifications in marsh beetles are illustrated and discussed.